Quality of life in cities – Empirical evidence in comparative European perspective. (October 2016) - Węziak-Białowolska, Dorota
Abstract: This study investigated aspects of urban quality of life in European cities. To this end, the Flash Eurobarometer 366: Quality of life in European cities was used. The survey provides opinions of 41 thousands inhabitants from 79 European cities, which enables analysis of interrelation between citizen characteristics, neighbourhood and city contexts and satisfaction with life in a city. The study analysed the following dimensions potentially related to satisfaction with life in a city: (1) availability of services, environment and social aspects in cities and neighbourhood; (2) socio-demographic factors; and (3) city characteristics such as economic development, labour market pressures, size, location, quality of institutions and safety. Findings indicated that satisfaction with life in a city varied considerably both inside cities and across Europe. Dissatisfaction with public transport, cultural facilities, availability of retail outlets, green space, air quality, trustworthiness of people, public administration and administrational efficiency, contributed significantly to dissatisfaction with life in a city. However, when citizens felt secure and satisfied with their place of living, they were also more likely to be satisfied with life in a city. Finally, cities with high percentage of people satisfied with safety in a city tended to be those in which citizens were also more satisfied with life in a city. Highlights: Satisfaction with city life varies considerably both inside cities and across Europe Specific aspects of city life are factors for dissatisfaction rather than satisfaction with city life Cities with high percentage of people satisfied with safety in a city tended to be those in which citizens were also more satisfied with life in a city Lack of trustworthiness and efficiency of public administration contribute to dissatisfaction with life in the city